2010
DOI: 10.2166/wst.2010.101
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour and adsorptive removal of siloxanes in sewage sludge biogas

Abstract: We investigated the behaviour of siloxanes, which adversely affect biogas engines, as well as their concentration levels in sewage sludge biogas in Japan. We also performed experiments on the absorptive removal of siloxanes using various adsorbents and determined the main adsorbent characteristics required for the removal of siloxanes. The results of our study on the concentration and composition of siloxanes in biogas were similar to previous reports. Moreover, we found that the concentration of siloxanes cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 10 publications
4
40
0
Order By: Relevance
“…The adsorption capacities determined experimentally are in agreement or even better than literature data concerning siloxane removal by silica gel [11,15,18,19].…”
Section: Influence Of the Adsorbent Bed Heightsupporting
confidence: 85%
See 3 more Smart Citations
“…The adsorption capacities determined experimentally are in agreement or even better than literature data concerning siloxane removal by silica gel [11,15,18,19].…”
Section: Influence Of the Adsorbent Bed Heightsupporting
confidence: 85%
“…They postulated that the siloxane concentrations may vary on a daily basis due to adsorption onto the gas collection pipework during the cooler night, followed by desorption when the sun comes up during the morning. Oshita et al [18] also found that the concentration of siloxanes changes in relation to the outside air temperature in a biogas from a waste water treatment plant. They concluded to an adsorption on the inner surface of the gas pipe or gasholder when the external temperature decreases.…”
Section: Influence Of the Adsorbent Bed Heightmentioning
confidence: 95%
See 2 more Smart Citations
“…The performance of adsorption is highly dependent on the molecular size of each siloxanes and the pore distribution of adsorbents, the carbon-based adsorbents with micro-pores are more efficient at removing L2 than D4 or D5, while non-carbon adsorbents that have meso or macro-pores are proper for D4 and D5 adsorption [9]. It was concluded that the adsorbents with large BET-specific surface areas and pH value are desired for the removal of siloxanes [10,11]. The siloxanes removal efficiency could reach 90-99% by solid adsorption technology, while the adsorbents are usually non-selective and the humidity will decrease the treatment efficiency of activated carbon.…”
Section: Siloxanes Removal Technologies From Biogasmentioning
confidence: 99%